Self-Cleaned Photonic-Enhanced Solar Cells with Nanostructured Parylene-C - Centeno, Pedro (2020)
Foundation for Science and Technology. Grant Number: UID/CTM/50025/2019 SuperSolar. Grant Number: PTDC/NAN-OPT/28430/2017 TACIT. Grant Number: PTDC/NAN-OPT/28837/2017 LocalEnergy. Grant Number: PTDC/EAM-PEC/29905/2017 FCT. Grant Number: SFRH/BD/148078/2019